Impact of Percutaneous Coronary Intervention and Implantation of Intra-Aortic Balloon Pump on the Outcome of an Acute Total Obstruction of the Left Main Coronary Artery - Hamza Hamayel; Yahya Ismail; Sajed Majadla; Yousef Hamshari; Yunis Daralammouri (Case Reports in Cardiology)
Background. Acute total occlusion of the left main coronary artery (LMCA) is a fatal event; most patients die before reaching hospitals. Few of them reach the hospital alive. Revascularization of the LMCA can be achieved by surgical intervention or percutaneous coronary intervention with unknown optimal modality. However, mortality of those patients is very high even with either; few cases reported successful management of acute total occlusion of the LMCA including our patient. Case Presentation. A 56-year-old male patient who is a smoker presented with typical chest pain worsened 2 hours prior to admission. He was hemodynamically stable, but he had respiratory failure due to pulmonary edema. An electrocardiogram showed anterior ST-elevation myocardial infarction. He was given loading doses of dual antiplatelet agents, in addition to respiratory support, then transferred immediately to the cardiac catheterization laboratory. Urgent cardiac catheterization showed total occlusion of the LMCA. Recanalization was done successfully, and a stent was inserted in the LMCA and left anterior descending artery. The patient developed cardiogenic shock during the procedure. An intra-aortic balloon pump (IABP) was applied which improved his hemodynamic status and enhanced his coronary flow. He is clinically improved, there was resolution of ST elevation, and cardiogenic shock gradually resolved. IABP was removed, and the patient was discharged in good general condition. Conclusions. Survival after acute total occlusion of the LMCA is very rare. The good outcome in this patient is attributed to early recognition and timely successful intervention, with good respiratory and hemodynamic support. The surgical and anaesthesia team should be on stand-by until complete revascularization and stabilization of the patient are achieved.